2012
DOI: 10.1158/1055-9965.epi-12-0585
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Total and Ionized Serum Calcium and Time to Fatal Prostate Cancer

Abstract: Background: Higher levels of total and ionized serum calcium have been shown to predict fatal prostate cancer in prospective studies. Because the follow-up time in these studies was relatively short, these associations could reflect the effect of clinically significant but occult prostate tumors on serum calcium levels. If this were true, prostate cancer mortality rates among men with higher levels of serum calcium should be higher during the early follow-up period and should decline thereafter.Methods: We tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Recently, the World Cancer Research Fund International concluded that evidence linking high calcium intake to PCa risk is limited [23], but the results of the current work are consistent with many other studies that demonstrated that high calcium intake increases risk of PCa [3, 5, 6, 13] as well as reports showing associations between high serum calcium levels and increasing PCa risk and risk of fatal PCa [24, 25]. Epidemiologic evidence also does not provide definitive support for an inverse association between vitamin D and PCa [2628], and other studies that explored the relationship between vitamin D intake and PCa did not find significant associations [5, 7].…”
Section: Discussionsupporting
confidence: 89%
“…Recently, the World Cancer Research Fund International concluded that evidence linking high calcium intake to PCa risk is limited [23], but the results of the current work are consistent with many other studies that demonstrated that high calcium intake increases risk of PCa [3, 5, 6, 13] as well as reports showing associations between high serum calcium levels and increasing PCa risk and risk of fatal PCa [24, 25]. Epidemiologic evidence also does not provide definitive support for an inverse association between vitamin D and PCa [2628], and other studies that explored the relationship between vitamin D intake and PCa did not find significant associations [5, 7].…”
Section: Discussionsupporting
confidence: 89%
“…For example, Nox5 activity is strongly enhanced by binding of Ca 2+ to the N‐terminal region of Nox5 . In this respect it may be noted that a large body of evidence suggests that increased calcium intake is associated with enhanced PCa risk . Moreover, the Ca 2+ channel TRPV6, which is overexpressed in PCa and correlates with tumor progression and poor prognosis, is also expressed at higher levels in the Nox5‐positive PCa cell lines PC‐3 and LNCaP compared to normal and benign epithelial cells .…”
Section: Discussionmentioning
confidence: 99%
“…We found higher corrected serum calcium levels in our population to be significantly associated with better survival. Research has noted these variables to be inversely related, typically in the setting of hypercalcemia associated with bone metastases and more advanced disease [ 32 , 33 ]. Our mean corrected serum calcium was 9.2 mg/dl which is within the normal limits of 8.5 to 10.1 mg/dl.…”
Section: Discussionmentioning
confidence: 99%